COMMUNICATION SKILLS THROUGH THE LANGUAGE OF SPEECH - Husain Abas, Raaed (ALBAHITH ALALAMI, 2007)
Language is the realistic and sensitive basis for any communication between two or more parties. It is an important workshop that prepares meanings and coding them according to a linguistic structure governed by agreed rules that speak to and coexist with everyone. Whereas the forms of communication are: personal, mediator and mass, none of them can move away from language in their dealings and communication patterns. Since each has its own characteristics and skills, it must be launched in its fields through verbal and non-verbal symbols and wears the elements of influential language as intended. It makes the recipient face two things: whether he fails to understand those symbols hence its purpose fail, or he meditates simply and lively, so that it corresponds to what the communicator wants. Language is a social activity, its speech is made up of the fabric of the environment in which she operates, and mass communication is at the center of that activity. It is a social unit that transmits ideas and knowledge between communities. Technological advances have provided it with that transfer and it also benefits in this field the language of discourse to use multiple skills and renewable and presentation methods in which the format is proportional to the content to achieve the goals and functions of mass communication. This research illustrates that use.